2017
DOI: 10.1136/sextrans-2016-052884
|View full text |Cite
|
Sign up to set email alerts
|

Probability of vertical transmission ofChlamydia trachomatisestimated from national registry data

Abstract: infections in infants were rare, with a population-based occurrence of 0.22 per 1000 live births. The risk of vertical transmission of in the population was<2%, which is significantly lower than reported earlier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…Data from two national health registries in Finland suggest that the risk of C. trachomatis disease related to vertical transmission in newborns was only 1.8% in their population. 22 That study was based on microbiological diagnosis of symptomatic newborns and did not take subclinical and empirically treated infections into account. The study provides an underestimation of MTCT because most nasopharyngeal infections are asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Data from two national health registries in Finland suggest that the risk of C. trachomatis disease related to vertical transmission in newborns was only 1.8% in their population. 22 That study was based on microbiological diagnosis of symptomatic newborns and did not take subclinical and empirically treated infections into account. The study provides an underestimation of MTCT because most nasopharyngeal infections are asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al reported that 32% of the infants in their patient series who were suffering from vertically transmitted chlamydial conjunctivitis had blood‐stained discharge from the infected eyes . We showed in a previous register‐based nationwide study in Finland that vertically transmitted C trachomatis infections in children were rare , and we thus assumed that C trachomatis infections may be underdiagnosed in the neonatal period. In the present study, however, it transpired that C trachomatis was not diagnosed in any of the 163 consecutive neonates with clinical conjunctivitis in a population‐based setting.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we highlight that even though we did not find any association between CT and prematurity, previous studies show that CT can be vertically transmitted (22). Besides,…”
Section: Discussioncontrasting
confidence: 66%